SIFAT FISIK DAN IDENTIFIKASI KANDUNGAN SENYAWA KIMIA CUKA KAYU (Wood vinegar) ALABAN - Ayu Manipa Putri; Violet Violet; Noor Mirad Sari (Jurnal Sylva Scienteae, 2022)
There are many charcoal productions in Indonesia whose smoke has not been utilized, even though the smoke can be obtained as liquid smoke (wood vinegar). The purpose of this study is to analyze the physical properties of wood vinegar and identify the components of wood vinegar chemical compounds using GC-MS testing from grade 3 to grade 1 levels using the distillation process. The results showed that testing the physical properties of wood vinegar for Specific Gravity (grade 3 and grade 1 with a value of 1.0281) and the results of the pH test (for grade 1 with a value of 4) did not meet Japanese standards. The results of the grade 3 Gross Content (transparency) test that have not been purified show a cloudy color and there is suspense, while grade 1 is according to Japanese standards because it is not cloudy and there is no suspense. While grade 1 is according to Japanese standards because it is not cloudy and there is no suspense. The results of the wood vinegar color test from the grade 3 distillation process are blackish brown because the Alaban wood contains several chemical components and after going through distillation it changes color to a faint clear-yellow color and meets Japanese standards. The results of the quality analysis of grade 3 wood vinegar have a very pungent odor, while the Japanese standard does not require the smell in the wood vinegar liquid. The test results of grade 3 alaban wood vinegar compounds contain 13 chemical commonents. Where the most dominant chemical compounds are acetic chemical compounds, phenol, 2-propanone, 2 (3H)-furanone, propanoic acid. The results of the identification of chemical compounds of alaban wood vinegar at grade 1 there are 22 compounds, the most dominant compounds are nerol compounds, beta-citronellol, citronella, citral, linalyl acetate.Banyak produksi arang di Indonesia yang asapnya belum termanfaatkan, padahal asap tersebut dapat dioleh sebagai asap cair (cuka kayu). Tujuan penelitian ini untuk menganalisa sifat fisik cuka kayu dan mengidentifikasi komponen senyawa kimia cuka kayu dengan menggunakan pengujian GC-MS dari tingkatan grade 3 menjadi grade 1 menggunakan proses destilasi. Hasil penelitian menunjukan bahwa pengujian sifat fisik cuka kayu untuk Berat Jenis (grade 3 dan grade 1 dengan nilai 1,0281) dan hasil uji pH (untuk grade 1 dengan nilai 4) belum memenuhi standar Jepang. Hasil uji Kadar Kotor (transparansi) grade 3 yang belum dimurnikan menunjukan warna keruh dan ada suspense, sedangkan grade 1 sesuai standar Jepang karena tidak keruh dan tidak ada suspense. Hasil pengujian warna cuka kayu dari proses penyulingan grade 3 berwarna coklat kehitaman karena di dalam kayu Alaban mengandung beberapa komponen kimia dan setelah melalui destilasi berubah warna menjadi bening-kuning samar dan memenuhi standar Jepang. Hasil analisis kualitas cuka kayu grade 3 memiliki bau yang sangat menyengat, sedangkan standar Jepang tidak mensyaratkan bau pada cairan cuka kayu. Hasil pengujian senyawa cuka kayu alaban grade 3 mengandung komonen kimia sebanyak 13 senyawa. Dimana senyawa kimia yang paling dominan adala senyawa kimia Acetic, Phenol, 2-propanone, 2 (3H)-furanone, propanoic acid. Hasil identifikasi senyawa kimia cuka kayu alaban pada grade 1 terdapat 22 senyawa, senyawa yang paling dominan adalah senyawa Nerol, Beta-Citronellol, Citronella, Citral, Linalyl Acetate